Indications and efficacy of endoscopic vacuum‐assisted closure therapy for upper gastrointestinal perforations. Issue 4 (15th November 2016) - Ooi, Geraldine; Burton, Paul; Packiyanathan, Andrew; Loh, Damien; Chen, Richard; Shaw, Kalai; Brown, Wendy; Nottle, Peter
Abstract : Background: Endoscopic vacuum‐assisted closure (EndoVAC) therapy is a recent innovation described for use in upper gastrointestinal perforations and leaks, with reported success of 80–90%. It provides sepsis control and collapses the cavity preventing stasis, encouraging healing of the defect. Whilst promising, initial reports of this new technique have not established clear indications, feasibility and optimal technique. Methods: We analysed all patients who underwent EndoVAC therapy between 2014 and 2016. The technique involved a standard gastroscope, nasogastric tube and vacuum‐assisted closure dressing kit, with endoscopic placement of the polyurethane sponge. Data were collected on indication, technique, sepsis control, outcomes and drainage volumes. Results: Ten patients were treated. Average age was 56.7 ± 12.3 years. There were three mortalities. EndoVAC placement was feasible in nine patients and successful healing was observed in six patients. Failure was more likely in the cases of large (>8 cm), chronic or complex cavities. A three‐phase response was seen in successful cases, with initial reduction in external drainage (average: 143–17 mL/day within 1 week), followed by a progressive reduction in inflammatory markers (2 weeks) and finally a healing phase with reduction in cavity size (3 weeks). Conclusion: EndoVAC therapy is a potentially useful adjunct to conventional treatments of a subset of upper gastrointestinal leaks and perforations when there is a contained cavity <8 cm. It appears less effective in an uncontained perforation or chronically established tract. It has clear advantages of being easily applied with readily available equipment and disposables.